97P Impact of prior lines of systemic therapy (PST) on the efficacy of cemiplimab, a human monoclonal anti–PD-1, in patients (pts) with advanced cutaneous squamous cell carcinoma (CSCC). (15th December 2019) - Rischin, D; Khushalani, N I; Schmults, C D; Guminski, A; Chang, A L S; Lewis, K D; Lim, A M; Hernandez-Aya, L; Hughes, B G M; Schadendorf, D; Hauschild, A; Stankevich, E; et al.
Abstract: Background: Cemiplimab demonstrated antitumour activity and an acceptable safety profile in a phase II study of pts with CSCC (NCT02760498). Here, we report efficacy by PST. Methods: The primary objective of the study is to evaluate the objective response rate (ORR) by independent central review (ICR). Pts with metastatic CSCC (mCSCC; Group 1) and locally advanced CSCC (Group 2) received 3 mg/kg Q2W for 96 weeks, and mCSCC received 350 mg Q3W for 54 weeks (Group 3). Data cutoff dates were 20 September 2018 (Groups 1 and 3) and 10 October 2018 (Group 2). Results: Of the 193 pts enrolled, 128 had cemiplimab as first-line therapy (1LT) and 65 had PST (table). Median follow-up was 9.4 months. The ORR per ICR was 46.9% (95% CI: 38.0–55.9; 17 complete responses [CR] and 43 partial responses [PR]) in pts with cemiplimab as 1LT and 38.5% (95% CI: 26.7–51.4; five CRs and 20 PRs) in pts with PST. The disease control rate per ICR was 75.8% (95% CI: 67.4–82.9) in pts with cemiplimab as 1LT and 64.6% (95% CI: 51.8–76.1) in pts with PST. Estimated 12-month duration of response (DOR) was 88.3% (95% CI: 73.9–95.0) among all 60-responding pts with cemiplimab as 1LT and 90.9% (95% CI: 68.1–97.6) among all 25-responding pts with PST. Estimated Kaplan–Meier 12-month progression-free survival was 56.9% (95% CI: 46.4–66.2) in pts with cemiplimab as 1LT and 46.7% (95% CI: 33.4–58.9) in pts with PST. 12-month overall survival was 90.7% (95% CI: 83.7–94.8) in pts with cemiplimab as 1LT and 76.3% (95% CI: 63.7–85.0) in pts with PST. The most common treatment-related adverse events in all pts were fatigue (n = 37, 19.2%), pruritus (n = 25, 13.0%) and diarrhoea (n = 24, 12.4%) and rash and maculopapular rash (both n = 21, 10.9%). Conclusion: As demonstrated by the numerically higher ORR, 12-month PFS, and OS, the efficacy of cemiplimab in advanced CSCC may be greater when used as 1LT, supporting its early use for patients with advanced CSCC. Clinical trial identification: NCT02760498. Editorial acknowledgement: Medical writing support under the direction of the authors was provided by Kate Carolan, PhD, of Prime (Knutsford, UK) and funded by Regeneron Pharmaceuticals, Inc. and Sanofi according to Good Publication Practice guidelines. Legal entity responsible for the study: Regeneron Pharmaceutical, Inc. and Sanofi. Funding: Regeneron Pharmaceutical, Inc. and Sanofi. Disclosure: D. Rischin: Research grant / Funding (institution), Non-remunerated activity/ies: Regeneron Pharmaceuticals, Inc.; Research grant / Funding (institution): Roche; Research grant / Funding (institution), Travel / Accommodation / Expenses, Non-remunerated activity/ies: Merck Sharp & Dohme; Research grant / Funding (institution), Non-remunerated activity/ies: Bristol-Myers Squibb; Research grant / Funding (institution), Non-remunerated activity/ies: GSK. N.I. Khushalani: Advisory / Consultancy, Research grant / Funding (self): Regeneron Pharmaceuticals, Inc.; Advisory / Consultancy: Bristol-Myers Squibb; Research grant / Funding (self): HUYA Bioscience International; Advisory / Consultancy: EMD Serono; Advisory / Consultancy: Genentech; Advisory / Consultancy, Data safety monitoring committee: AstraZeneca; Advisory / Consultancy: Merck; Advisory / Consultancy: ARRAY Biopharma; Advisory / Consultancy: Immunocore; Research grant / Funding (self): Merck; Research grant / Funding (self): Novartis; Research grant / Funding (self): GlaxoSmithKline; Research grant / Funding (self): Cellgene; Research grant / Funding (self): Amgen; Honoraria (self): Sanofi; Shareholder / Stockholder / Stock options: Bellicum Pharmaceuticals; Shareholder / Stockholder / Stock options: Mazor Robotics; Shareholder / Stockholder / Stock options: Amarin; Shareholder / Stockholder / Stock options: Transenetrix. C.D. Schmults: Advisory / Consultancy, Research grant / Funding (self), Steering committee member: Castle Biosciences; Advisory / Consultancy, Research grant / Funding (self), Steering committee member: Regeneron Pharmaceuticals, Inc.; Advisory / Consultancy: Sanofi; Research grant / Funding (self): Novartis; Research grant / Funding (self): Genentech; Research grant / Funding (self): Merck; Advisory / Consultancy, Chair for NCCN: NCCN. A. Guminski: Advisory / Consultancy, Travel / Accommodation / Expenses, Non-remunerated activity/ies: Bristol-Myers Squibb; Advisory / Consultancy, Travel / Accommodation / Expenses, Non-remunerated activity/ies: Sun Pharma; Advisory / Consultancy: Merck KGaA; Advisory / Consultancy: Eisai; Advisory / Consultancy: Pfizer; Non-remunerated activity/ies: Astellas; Research grant / Funding (institution), Clinical trial unit support: PPD Australia. A.L.S. Chang: Advisory / Consultancy, Research grant / Funding (self): Regeneron Pharmaceuticals, Inc.; Research grant / Funding (self): Novartis; Research grant / Funding (self): Galderma; Advisory / Consultancy, Research grant / Funding (self): Merck. K.D. Lewis: Research grant / Funding (self), Grants and personal fees: Regeneron Pharmaceuticals, Inc.. A.M. Lim: Non-remunerated activity/ies: Merck Sharp & Dohme; Travel / Accommodation / Expenses: Bristol-Myers Squibb. L. Hernandez-Aya: Advisory / Consultancy: Massive Bio; Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Sanofi; Speaker Bureau / Expert testimony, Research grant / Funding (self), Travel / Accommodation / Expenses: Regeneron Pharmaceuticals, Inc.; Research grant / Funding (self), Travel / Accommodation / Expenses: Bristol-Myers Squibb; Research grant / Funding (self): Immunocore; Research grant / Funding (self): Merck Sharp & Dohme; Research grant / Funding (self): Polynoma; Research grant / Funding (self): Corvus Pharmaceuticals; Research grant / Funding (self): Roche; Research grant / Funding (self): Merck Serono; Research grant / Funding (self): Amgen; Research grant / Funding (self): MedImmune; Research grant / Funding (self): Takeda. B.G.M. Hughes: Advisory / Consultancy: Merck Sharp & Dohme; Advisory / Consultancy: Bristol-Myers Squibb; Advisory / Consultancy: AstraZeneca; Advisory / Consultancy: Pfizer; Advisory / Consultancy: Roche; Advisory / Consultancy: Eisai; Advisory / Consultancy: Merck; Research grant / Funding (institution): Amgen. D. Schadendorf: Research grant / Funding (institution): Regeneron Pharmaceuticals, Inc.; Advisory / Consultancy: Amgen; Advisory / Consultancy: Leo Pharma; Speaker Bureau / Expert testimony: Boehringer Ingelheim; Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution), Patients' fees: Roche; Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution), Patients' fees: Novartis; Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution), Patients' fees: Bristol-Myers Squibb; Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution), Patients' fees: Merck-EMD; Advisory / Consultancy, Speaker Bureau / Expert testimony: Incyte; Advisory / Consultancy, Speaker Bureau / Expert testimony: Pierre Fabre; Advisory / Consultancy, Research grant / Funding (institution), Patients' fees: MSD; Advisory / Consultancy, Steering committee honorarium: 4SC; Advisory / Consultancy: AstraZeneca; Advisory / Consultancy: Pfizer; Advisory / Consultancy: Array; Advisory / Consultancy, Research grant / Funding (institution), Patients' fees: Philiogen. A. Hauschild: Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution): Amgen; Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution): Bristol-Myers Squibb; Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution): MSD/Merck; Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution): Pierre Fabre; Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution): Provectus; Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution): Roche; Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution): Novartis; Advisory / Consultancy, Research grant / Funding (institution): Merck Serono; Advisory / Consultancy, Research grant / Funding (institution): Philogen; Advisory / Consultancy, Research grant / Funding (institution): Regeneron Pharmaceuticals, Inc.; Advisory / Consultancy: OncoSec. E. Stankevich: Shareholder / Stockholder / Stock options, Full / Part-time employment: Regeneron Pharmaceuticals, Inc.. J. Booth: Shareholder / Stockholder / Stock options, Full / Part-time employment: Regeneron Pharmaceuticals, Inc.. S. Li: Shareholder / Stockholder / Stock options, Full / Part-time employment: Regeneron Pharmaceuticals, Inc.. Z. Chen: Shareholder / Stockholder / Stock options, Full / Part-time employment: Regeneron Pharmaceuticals, Inc.. J. Desai: Shareholder / Stockholder / Stock options, Full / Part-time employment: Regeneron Pharmaceuticals, Inc.. I. Lowy: Shareholder / Stockholder / Stock options, Full / Part-time employment: Regeneron Pharmaceuticals, Inc.. M.G. Fury: Shareholder / Stockholder / Stock options, Full / Part-time employment: Regeneron Pharmaceuticals, Inc.. M.R. Migden: Honoraria (self), Research grant / Funding (institution), Travel / Accommodation / Expenses: Regeneron Pharmaceuticals, Inc.; Honoraria (self), Research grant / Funding (institution), Travel / Accommodation / Expenses: Novartis; Honoraria (self), Research grant / Funding (institution), Travel / Accommodation / Expenses: Genentech; Honoraria (self), Research grant / Funding (institution), Travel / Accommodation / Expenses: Eli Lilly; Honoraria (self), Travel / Accommodation / Expenses: Sun Pharma.